APPLYING THE STRATEGIES OF DISAGREEMENT EXPRESSION IN THE MOVIE OF AARON SORKIN’S A FEW GOOD MEN - Ahmad Febrianto Okem; Ni Ketut Mirahayuni (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2018)
This study talks about the forms and strategies of disagreement expressions used by the characters in in Movie Script Aaron Sorkin’s A Few Good Men. The aims of this research are to find out the forms and types of disagreement strategies. The descriptive qualitative was used in this research and the data were the conversation among the characters. The analysis was based on Muntigl and Turnbull’s (1998) for the types of disagreement strategies in disagreement expression and for the types of the form based on Liu’s (2004). The study involves thirty (30) data taken from drama plays. The study found that (1) disagreement expression can be identified by the form to describe the type of the sentence, they are declarative form involves twenty three (23) data of disagreement expression which is found in all types of disagreement strategy, (2) Interrogative form involves four (4) data of disagreement expression which is found in challenge and counterclaims strategy. (3) Imperative form involves two (2) data of disagreement expression which is found in challenge strategy (4) Exclamative form involves one (1) data of disagreement expression which is found in contradict strategy. Second, the result of the analysis also shows that there are four types of disagreement strategies usually used by the characters: Irrelevancy Claims involves four (4) data, Challenge involves nine (9) data, Contradict involves nine (9) and Counterclaims involves eight (8) data.